Teacher education for rural communities: A focus on 'Incentives' - White, Simone; Green, Bill; Reid, Joanne; Lock, Graeme; Hastings, Wendy; Cooper, Maxine (Melbourne, 2008)
In Australia we face a national crisis in attracting and retaining teachers and other professionals with regard to rural areas. In response to this difficulty in ‘staffing the empty schoolhouse’ (Roberts 2004), the majority of state education departments have initiated some form of rural incentive scheme designed to attract teachers to rural schools. This paper argues that such schemes have little chance of success unless teachers taking up such incentives have actually been prepared for teaching in nonmetropolitan schools. Although many universities claim to prioritise rural and regional education and community development as part of their vision statements, in reality relatively few education providers reflect this rhetoric in their practice and only a handful have made direct links to such state-based schemes in pre-service teacher education, or initiated their own rural incentives. A preliminary study into pre-service preparation and rural incentive schemes, as part of a three-year ARC Discovery Grant, indicates that, nationally, the majority of Faculties and Schools of Education have no easily accessible or advertised incentive programs to encourage students to undertake a rural practicum. Nor do many reflect rural education in their course-work. This paper will introduce the ‘TERRAnova’ project, and then discuss findings of the preliminary work to date that has focussed on identifying incentives and their significance. Drawing on evidence collected from websites from Australian Universities representing all pre-service teacher education programs in the nation, we argue that few Faculties and Schools appear to see it necessary or desirable to provide students with links to information about particular state-based rural funding opportunities. We show how some, either directly or indirectly, imply the importance of a rural practicum, and that a few teacher education programs provide written advice to students who are considering taking up a rural practicum. It is unclear, however, whether follow-up advice is ...